Transitioning to low carbon construction: a review of blast and fragmentation impact research related to terrorist threats - Laycock, Angela; Helliker, Aimee; Critchley, Richard; Hazael, Rachael (Elsevier, 2025)
As countries tackle climate change by aiming to reach net-zero carbon, the construction industry faces a substantial challenge to reduce carbon emissions in infrastructure, whilst maintaining safety standards. This review initially explores the sustainability targets and the evolving terrorist threat landscape and trends. A systematic search identifies research publications around blast and ballistic/fragmentation impact testing of materials. It then focusses on low carbon material variants, ‘carbon sink’ products and materials where design efficiency can reduce carbon content. Whilst this review shows that blast, ballistic and impact performance research of low carbon construction materials is a growing topic, currently the testing of products against relevant threats lags implementation. Design and test standards for these materials are still limited, resulting in difficulties for building owners to assess the risk and implement an adequate safety plan against terrorist threats. The greatest area where research and test standards are lacking is around cladding, especially for modular or off-site buildings which have a wide variety of material options. This review concludes with suggestions for further research to understand the vulnerabilities of these building materials against terrorist threats.
Keywords: 4005 Civil engineering; Sustainable; Net zero carbon; Material performance; Explosion; Bomb; Ballistic